PERANCANGAN BUKU BERBENTUK BULLET JOURNAL TENTANG KULINER KHAS AMBON - Yana Erlyana; Brandon William Sipasulta (Universitas Mercu Buana, 2023)
The design of this final task served to introduce the large masses the unique food of the town of Ambon in order to preserve the traditional culinary areas. Because many still do not know that much of the food from Ambon is unique and worth tasting and still lack of media information about the culinary region. Research methods are conducted using qualitative descriptive research with data collection of interviews, questionnaires, library studies and observations. As a result of the questionnaires being distributed online, the authors found that 153 respondents feel that Indonesia has an interesting tourist attraction, one of which is the culinary tour of Ambon, in which ambon's culinary tour is still poorly known and the media information is inadequate. Respondents agree that books can be one of the good information media, so Ambon's typical culinary book is prepared by adapting the Bullet journal form and other supporting media to be more attractive and interactive. It is hoped that this design will enable the cuisine of the region especially of the city of Ambon to be better known and preserved.